German Center Subanalysis of the LEVANT 2 Global Randomized Study of the Lutonix Drug-Coated Balloon in the Treatment of Femoropopliteal Occlusive Disease. (June 2016) - Scheinert, Dierk; Schmidt, Andrej; Zeller, Thomas; Müller-Hülsbeck, Stefan; Sixt, Sebastian; Schröder, Henrik; Weiss, Norbert; Ketelsen, Dominik; Ricke, Jens; Steiner, Sabine; Rosenfield, Kenneth
Purpose: To report a subanalysis of the German centers enrolling patients in the prospective, global, multicenter, randomized LEVANT 2 pivotal trial ( ClinicalTrials.gov identifier NCT01412541) of the Lutonix drug-coated balloon (DCB) for the treatment of femoropopliteal occlusive disease.Methods: Among the 476 patients in LEVANT 2, 126 patients (mean age 67.1±9.6 years; 79 men) were enrolled at the 8 participating German sites between August 2011 and July 2012 and were randomized 2:1 to treatment with the Lutonix DCB (n=83) vs an uncoated balloon during percutaneous transluminal angioplasty (PTA, n=43). All patients had intermittent claudication or rest pain (Rutherford categories 2–4). Average lesion length was 58 mm and average treated length was 100 mm. Severe calcification was present in 11% of lesions, and 23% were total occlusions. The efficacy outcome was primary patency at 12 months, and the safety outcome was 12-month freedom from a composite of perioperative death, index limb–related death, amputation (below or above the ankle), and index limb revascularization. Secondary endpoints included target lesion revascularization (TLR), major adverse events, and functional outcomes.Results: Demographic, clinical, and lesion characteristics were matched between Lutonix DCB and PTA groups, as were the final percent diameter stenosis (19%) and procedure success (91%). By Kaplan-Meier analysis, the 12-month primary patency rate was 80% vs 58% (p=0.015) and the composite safety endpoint rate was 94% vs 72% (p=0.001), respectively. Freedom from TLR was higher for DCBs (96%) vs PTA (82%, p=0.012). Major adverse events were similar for both groups. The benefit favoring DCB over PTA was observed in German men and women. Compared to the non-German LEVANT 2 cohort, there was a shorter time between insertion and inflation of treatment balloons (21.8 vs 39.5 seconds, p<0.001) in the German cohort. Balloons were inflated to higher pressures (9.0 vs 7.7 atm, p<0.001) but for a shorter period of time (130 vs 167 seconds, p<0.001), and although treated lesions in the German cohort had a higher baseline stenosis, final postprocedure diameter stenosis was lower (19% vs 22%, p=0.04) than in the non-German patients.Conclusion: Superiority of DCB over PTA in the German cohort of LEVANT 2 was demonstrated for primary patency, composite safety, and freedom from TLR. The benefit of DCB was also consistent for both genders. Geographic or regional differences in procedural variables may account for the different outcomes between the German and non-German cohorts.